Parents’ and Childcare Workers’ Perspectives Toward SARS-CoV-2 Test and Surveillance Protocols in Pre-school Children Day Care Centers: A Qualitative Study Within the German Wü-KiTa-CoV Project - Gierszewski, David; Kurotschka, Peter Konstantin; Krauthausen, Maike; Fröhlich, Willi; Forster, Johannes; Pietsch, Franziska; Streng, Andrea; Rücker, Viktoria; Wallstabe, Julia; Hartmann, Katrin; Jans, Thomas; Engels, Geraldine; et al. (Frontiers in Medicine, 2022)
Background: Feasibility of surveillance through continuous SARS-CoV-2 testing in pre-school children and childcare workers (CCWs) to prevent closure of day care centers (DCCs) was proven in the Wü-KiTa-CoV study. The purpose of this study was to describe the factors that facilitate or hinder the implementation of continuous SARS-CoV-2 testing from the perspective of parents and CCWs involved in the study. Methods: A total of 148 semi–structured telephone interviews, repeated before and after the implementation of the surveillance protocols, were conducted with parents and CCWs belonging to the DCCs involved in Wü-KiTa-CoV and analysed using qualitative content analysis. Results: Five main topical categories that influences implementation of surveillance protocols for SARS-CoV-2 in DCCs emerged: Generating valuable knowledge, Impact on daily life, Communication and information, Children’s wellbeing and the Sense of security. Smooth integration in daily routines, quickly delivered test results, and efficient communication and information between the study team and the participants were identified as factors that had a positive impact on implementation. To ensure children's well-being, the introduction of non-invasive testing procedures such as saliva testing, parental involvement to motivate and prepare children for the procedure, the creation of a child-friendly environment for testing, and use of child-friendly explanations were considered critical. The surveillance was found to increase the sense of security during the pandemic. Conversely, reliability of tests in the surveillance protocols, low participation rates, non-transparent communication, the need to travel to testing sites, fear of quarantine in case of positive test results, concerns about higher workloads, the fear of unpleasant feelings for children, their young age, and changing test teams were considered as hindering factors. Conclusions: This qualitative study of parents of children in day care and DCC staff under surveillance through continuous testing for SARS-CoV-2 in nine German DCCs identified several factors that facilitate or hinder its implementation. These should be considered when planning screening interventions to prevent the spread of SARS-CoV-2 or other infectious diseases in pre-school children DCCs.